Parâmetros genéticos e seleção de linhagens de feijão mesoamericano para a concentração de fósforo, ferro, zinco e fitatos - Steckling, Skarlet de Marco (2018)
The knowledge of genetic parameters of characters that minimize the antinutritional effect of phytates, and that help in the development of biofortified common bean cultivars for phosphorus, iron and zinc, is contributes to reduce the deficiencies of these minerals in the population. Therefore, the objectives of this work were: (1) to obtain estimates of heritability for concentration of phosphorus, iron, zinc and phytates in F5:6 and F5:7 bean lines of the Mesoamerican group; (2) to analyze the inheritance pattern of phosphorus, iron, zinc and phytate concentrations in F5:6 and F5:7 Mesoamerican beans; and (3) to select F5:6 and F5:7 lines with high phosphorus, iron and zinc concentrations and low concentration of phytates in Mesoamerican bean grains. For this, 100 bean lines obtained from the previous cross between BRS Esteio × SCS205 Riqueza parental were used, which were contrasting for iron and zinc and tegument coloration. Segregant populations were evaluated in two field experiments in the experimental area of the Bean Breeding Program of the Federal University of Santa Maria, Santa Maria-RS. At the beginning of 2017, under the augmented block designs, 103 treatments were analyzed, of which 100 were lineages of the generation F5:6, the parents and the cultivar Pérola. The experiment was carried out in the 2017/2018, and conducted in the 11 x 11 simple lattice design, evaluated a total of 121 treatments, where 100 were F5:7 generations, the parental and 19 cultivars. . High heritability estimates were generated in F5:6 for all minerals and phytate of the evaluated strains, surpassing 97,47%. While the generation F5:7, is a variable of variable heritability of low magnitude for phosphorus (30,31%) the high for phytates (73,63%). The combinations of phosphorus, iron, zinc and phytate are the quantitative inheritance, evidencing one of many genes in the control of these characters. The L33-17 and L55-17 lines are considered sequences of phosphorus, iron and zinc in the generation F5:6, and high concentration of zinc and phytate low in the same generation, was verified in the L1-17 and L61-17 lines. In the F5:7 generation, the L34-17, L65-17, L61-17 and L89-17 lines receive the minerals from the minerals within the range expected for Mesoamerican group bean grains. The L56-17 line (generation F5:7) showed a high iron concentration. No line has low phytate content in generation F5:7. The L61-17 line has phosphorus, iron, zinc units higher than the lines mean and low concentration of phytate in the grains and should be selected by the Breeding Program.